2020
DOI: 10.1002/hon.2778
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of histologic grade and Ki‐67 proliferation index in follicular lymphoma

Abstract: The prognostic value of histologic grading and the Ki-67 proliferation index in follicular lymphoma (FL) is controversial. This study investigated the clinical usefulness of these two factors in Asian FL patients. Four hundred and thirty-three patients diagnosed with FL were retrospectively reviewed with a median follow-up time of 47.0 months (range, 24.0-168.0). The 10-year overall survival (OS) rate and progression-free survival (PFS) rate were 91.0% and 47.1%, respectively. Grade 3B and grade 3B with diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
1
13
2
Order By: Relevance
“…Biologically, FL grade 3B, compared with grade 3A, is often IRF4/MUM1 positive but CD10 negative and less likely to harbor Bcl2 rearrangement [10]. Moreover, patients with FL grade 3B or 3B with DLBCL were associated with a higher level of Ki-67 than those of FL grade 3A [11]. This support the concept the underlying genetic events were different between these two subtypes.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Biologically, FL grade 3B, compared with grade 3A, is often IRF4/MUM1 positive but CD10 negative and less likely to harbor Bcl2 rearrangement [10]. Moreover, patients with FL grade 3B or 3B with DLBCL were associated with a higher level of Ki-67 than those of FL grade 3A [11]. This support the concept the underlying genetic events were different between these two subtypes.…”
Section: Discussionsupporting
confidence: 58%
“…Whereas we do observe a plateau in the PFS curve in aggressive FL. This could be explained by the fact that aggressive FL is a curable disease which was con rmed in a recent study showed a better PFS in aggressive FL compared with FL grade 3A [11].…”
Section: Discussionmentioning
confidence: 90%
“…Analysis shown for OS, where patients have been split into two groups based on the optimal cut points. Cut points were selected using the Contal & O’Quigley test [ 38 ] method. P Log Rank : significance for the log rank test and P C.O.…”
Section: Resultsmentioning
confidence: 99%
“…FLIPI was selected for multivariable analyses as a state-ofthe-art, widely validated prognostic index. We did not test histologic grade in multivariable analyses as its prognostic value for FL is limited and patients with grade 1-2 and 3a have similar survival rates [37][38][39]. Kaplan-Meier analysis for the diversity features was carried out by dichotomising the variables at the optimal cut point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation